2020
DOI: 10.1002/aur.2298
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Gait Analysis in Duplication 15q Syndrome and Nonsyndromic ASD

Abstract: Motor impairments occur frequently in genetic syndromes highly penetrant for autism spectrum disorder (syndromic ASD) and in individuals with ASD without a genetic diagnosis (nonsyndromic ASD). In particular, abnormalities in gait in ASD have been linked to language delay, ASD severity, and likelihood of having a genetic disorder. Quantitative measures of motor function can improve our ability to evaluate motor differences in individuals with syndromic and nonsyndromic ASD with varying levels of intellectual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…With regard to the nature of the first concerns, we found that initial developmental concerns were most often centered around delayed motor milestones. Earliest signs of developmental delay are more likely to present in the motor domain for individuals with an NDD and an associated genetic variant [ 22 , 23 ], suggesting that significant motor delay may increase the likelihood of a positive finding on genetic testing for patients with NDDs. It is important for physicians to be aware of this association, as it will allow for better prioritization of genetic testing and genetic referrals and allow for a more informed and nuanced discussion of the risks and benefit of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the nature of the first concerns, we found that initial developmental concerns were most often centered around delayed motor milestones. Earliest signs of developmental delay are more likely to present in the motor domain for individuals with an NDD and an associated genetic variant [ 22 , 23 ], suggesting that significant motor delay may increase the likelihood of a positive finding on genetic testing for patients with NDDs. It is important for physicians to be aware of this association, as it will allow for better prioritization of genetic testing and genetic referrals and allow for a more informed and nuanced discussion of the risks and benefit of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Although various factors could influence the locomotor activity of mice, reduced time spent for long locomotion in Emx1G6 15q dup mice might result from impaired motor planning and execution due to abnormal M2-related FC. While human dup15q syndrome shows a gait pattern of the slow pace, poor postural control, and large gait variability 40 and patients with paternal duplication in 15q11-13 display clumsy motor skill development 41 , 15q dup mice were also reported to display mild motor impairment such as longer stride length and reduced stride frequency, and deficits in motor learning and cerebellar synaptic plasticity 42 . Since recent studies demonstrate that cerebellar output modulates preparatory activity in the anterolateral motor cortex 43,44 , the abnormal M2-related FC we observed during behavior state transitions may also arise as a consequence of deficiency of a more widespread functional network, potentially including interactions with extracortical brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showcases translational and longitudinal use of quantitative motor metrics for a genetic NDD. Clinically, quantitative gait research has gained traction across many NDDs and the idea to tailor attention on gait in preclinical studies is now also gaining momentum (IDDRC working group, AGENDA working group, personal communications) for Rett syndrome, neurofibromatosis, Down syndrome, and other NDDs (Hampton et al, 2004;Jequier Gygax et al, 2020;Kennedy et al, 2020;Layne et al 2018;Rahn et al, 2020;Summers et al, 2015;Wilson et al, 2020). Data from our work showed analogous measures of gait phenotypes in rodents that are being quantified currently in AS clinics (Jessica Duis MD, personal communication).…”
Section: Discussionmentioning
confidence: 99%